2018
DOI: 10.1088/1475-7516/2018/01/005
|View full text |Cite
|
Sign up to set email alerts
|

A de Sitter tachyonic braneworld revisited

Abstract: Abstract. Within the framework of braneworlds, several interesting physical effects can be described in a wide range of energy scales, starting from high-energy physics to cosmology and low-energy physics. An usual way to generate a thick braneworld model relies in coupling a bulk scalar field to higher dimensional warped gravity. Quite recently, a novel braneworld was generated with the aid of a tachyonic bulk scalar field, having several remarkable properties. It comprises a regular and stable solution that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 100 publications
(139 reference statements)
2
11
0
Order By: Relevance
“…Employing the replacement of the supersymmetric operators by the specific solution of the field equations, we found that tachyon braneworld in the bulk negative/zero cosmological constant is stable under scalar fluctuations, which is consistent with that in [14][15][16]. We applied similar analysis to the instability of tachyonic braneworld model in the bulk positive cosmological constant.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Employing the replacement of the supersymmetric operators by the specific solution of the field equations, we found that tachyon braneworld in the bulk negative/zero cosmological constant is stable under scalar fluctuations, which is consistent with that in [14][15][16]. We applied similar analysis to the instability of tachyonic braneworld model in the bulk positive cosmological constant.…”
Section: Discussionsupporting
confidence: 76%
“…+k, (2.27) where the hypergeometric function 2 F 1 (a, b; c; z) is defined for |z| > 1 by the power series and a − b must not be an integer. Here, for 0 < n < 1 the tachyon field becomes real value by introducing a complex constant l. The warped factor f (x) is [15] f (x) = −n ln…”
Section: B λ5 = 0 Casementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors of Ref. [16] indicated that this tachyonic braneworld allows for a nontrivial solution with a vanishing 5D cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4,9]. Tachyonic 5D domain wall models can be implemented on smooth 5D branes [34][35][36] within the framework of cosmological inflationary scenarios [37,38]. Now we want to explore the tachyonic corrections to dynamical AdS/QCD holographic models [39], from the point of view of their underlying informational content.…”
Section: Introductionmentioning
confidence: 99%